Of poseidon eaudiobook - Banks, Anna (Of Poseidon, 2012)
Emma and her friend Chloe are spending their vacation in Florida. When Emma literally runs into a hot guy named Galen on the beach, little does she know he's a prince of the Syrena. Galen and Emma both feel something strange—is it attraction?—and Galen suspects that Emma might well be the girl he's heard of—a human who can communicate with fish. What follows is a deadly scene with a shark in which Galen witnesses Emma's gifts. He must know more about her, and follows her back to New Jersey, and high school, to find out for sure if she's the key to saving his kingdom. Soon, Emma can't deny her feelings for him, but she can't explain them either—and both she and Galen must learn more about where she comes from and what her powers are before they can trust one another and their feelings. Told from both Emma and Galen's points of view, here is a fish-out-of-water story that sparkles with intrigue, humor, and waves of romance.